SINERGITAS KOMUNITAS GUSDURIAN PASURUAN DENGAN LEMBAGA PENDIDIKAN TINGKAT SEKOLAH MENENGAH ATAS DALAM MEWUJUDKAN DUTA TOLERANSI SE-PASURUAN (STUDI KASUS DI KABUPATEN PASURUAN) - Evi Sukarti Ningsih; M. Anang Sholikhudin; Saifulah (Journal Multicultural of Islamic Education, 2021)
The ability to restrain oneself as a manifestation of this tolerant attitude will make a person have understanding and tolerance for different opinions. Differences of opinion are natural, they cannot be prohibited or suppressed, only that all parties understand that these differences must be handled wisely in accordance with the noble values ​​of their religious beliefs, culture, and traditions. In this study, the researcher used a qualitative approach with a case study approach. The Pasuruan Gusdurian Community is a community forum that was formed in December 2010, after Gus Dur's death in 2009. This community was formed because many young people are starting to get restless because of the many children who have high ideology and potential but have not found a suitable forum. right to continue, that's why Alisa Wahid daughter of KH. Abdurrahman Wahid, who is familiarly called Gus Dur, began to knit management to form a joint family from various groups that were not limited in any form, whether age, class, race, ethnicity, religion, and others. The management of the Gusdurian community was formed and inaugurated simultaneously with Khol 1. The design for the formation of the Gusdurian community started from children who had full intentions to study Gus Dur's morals and struggles without following practical politics.